The barriers to observing professional ethics in the practice of nursing care from nurses' viewpoints. (June 2021) - Azadian, Marzieh; Rahimi, Azar; Mohebbi, Mohammad; Iloonkashkooli, Raziyeh; Maleki, Maryam; Mardani, Abbas
Aims: This study aimed to investigate barriers in the observation of professional ethics during clinical care from a nursing viewpoint. Also, it examined the association between these barriers and nurse demographic variables. Methods: A descriptive-analytic design was carried out on 207 nurses working in selected hospitals within an urban area of Iran in 2019. Data were collected using a standard questionnaire containing 33 questions that measured barriers to observation of professional ethics. The questionnaire measures three domains of management, environment and individual care. Results: In the management dimension, the most important barrier preventing observation of professional ethics was the shortage of personnel. For the environmental dimension, biological changes due to working on the nightshift, and for the individual care dimension, a lack of time were the most important barriers preventing observation of clinical ethics. Findings additionally highlighted a significantly inverse association between barriers to observing professional ethics and the male gender, participating in the ethics workshop and high work-level experiences. Conclusions: It is suggested that nursing managers in hospitals correct and remove obstacles with careful planning and emphasis on principles and standards of care including environmental and managerial factors and training professional ethics to nurses.